2011
DOI: 10.1093/cercor/bhr013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Contributions to Regional Cortical Surface Area in Humans: A Magnetic Resonance Imaging Twin Study

Abstract: Cortical surface area measures appear to be functionally relevant and distinct in etiology, development, and behavioral correlates compared with other size characteristics, such as cortical thickness. Little is known about genetic and environmental influences on individual differences in regional surface area in humans. Using a large sample of adult twins, we determined relative contributions of genes and environment on variations in regional cortical surface area as measured by magnetic resonance imaging befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 40 publications
14
88
2
Order By: Relevance
“…Regional cortical volume (figure 2C) is the product of surface area (figure 2B) and average cortical thickness of a given region (figure 2A). Based on our findings, these two variables (thickness and surface area) are independent of each other, as also supported by previous studies on cortical morphology 31 32. Effects found with cortical volume are, therefore, diluted effects, caused either by changes in cortical thickness or surface area.…”
Section: Resultssupporting
confidence: 91%
“…Regional cortical volume (figure 2C) is the product of surface area (figure 2B) and average cortical thickness of a given region (figure 2A). Based on our findings, these two variables (thickness and surface area) are independent of each other, as also supported by previous studies on cortical morphology 31 32. Effects found with cortical volume are, therefore, diluted effects, caused either by changes in cortical thickness or surface area.…”
Section: Resultssupporting
confidence: 91%
“…This is consistent with previous findings regarding the heritability of the GM volume and thickness in the frontal and temporal lobes (Eyler et al, 2011; Hulshoff Pol et al, 2006; Joshi et al, 2011; Thompson et al, 2001). The common genetic factor related to schizophrenia was also shown in the pre-frontal (Cannon et al, 2002), frontal and temporal cortices (Cannon et al, 1998, Markov et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…E-mail: nschork@scripps.edu or amdale@ ucsd.edu. heritable (25-50%) (11,13). These studies reveal that genes have both global and regional effects on cortical surface area, which also seems to be true in mice.…”
Section: −8mentioning
confidence: 58%
“…Human twin studies have shown a significant genetic component to cortical volume (10)(11)(12) and surface area (>80% heritable) (13)(14)(15)(16), and the occipital proportion of cortex is also quite Conflict of interest statement: I.M. has received a speaker's honorarium from Janssen and AstraZeneca.…”
Section: −8mentioning
confidence: 99%